Hydrocephalus from Past to Nowadays - Ponomaryov, V.; Merkulova, O. (Psychiatry, Neurology and Medical Psychology, 2016)
The study and treatment of hydrocephalus all time exсited the physicians. Understanding the reasons of appearance and development of this diseases and also accomplish it anomalies of nervous system help create a system of adequate treatment. Untreated hydrocephalus has a survival rate of 40–50%, with the survivors having varying degrees of intellectual, physical, and neurological disabilities. Prognosis for treated hydrocephalus varies, depending on the cause. Early diagnostic and qualified treatment can improve the outcomes and prognosis of these patients